Recurrent, truncating SOX9 mutations are associated with SOX9 overexpression, KRAS mutation, and TP53 wild type status in colorectal carcinoma - Javier, Breanna M. (Oncotarget, 2016)
PURPOSE: The extent to which the developmental transcription factor SOX9 functions as an oncogene or tumor suppressor in colorectal carcinoma (CRC) is debatable. We aimed to clarify the effect of SOX9 mutations on SOX9 protein expression and their association with known molecular subtypes and clinical characteristics in advanced CRC. EXPERIMENTAL DESIGN: Next generation sequencing data (MSK-IMPACT) from CRC patients was used to interrogate SOX9, KRAS, NRAS, BRAF, TP53, APC, and PIK3CA. Mutant and wild type (WT) SOX9 cases underwent immunohistochemical (IHC) staining to assess protein expression. SOX9 allele-specific copy number was assessed by Affymetrix Oncoscan array. RESULTS: SOX9 was mutated in 38 of 353 (10.7%) CRC, of which 82% were frameshift or nonsense. Compared to SOX9 WT, SOX9 mutation was strongly associated with coexistent mutant KRAS (p=0.0001) and WT TP53 (p=0.0004). SOX9 was overexpressed in both SOX9 mutant and WT CRC. Among SOX9 mutants, the highest expression was noted for truncating exon 3 mutants (mean H scores 239±105 versus 147±119, p value=0.02). Further, SOX9 truncating mutants with loss of the WT allele demonstrated protein overexpression indicating the WT protein was not required for protein stabilization. CONCLUSIONS: SOX9 is overexpressed in CRC, including those with recurrent distal truncating mutations. The latter has structural similarity to the oncogenic isoform MiniSOX9, which is distally truncated due to aberrant splicing. This information suggests that truncated SOX9 has oncogenic features. SOX9 mutations are highly enriched in KRAS mutant and TP53 wild type CRC; and may provide a therapeutic target in approximately 11% of CRC.